Забезпечення презумпції відповідності. Спеціальні вимоги до призначених органів з оцінки відповідності - Фоменко, В. Д. (My University, 2020)
The given work is devoted to presumption of conformity. The system of technical regulation (metrology, standardization, conformity assessment, market surveillance) aims at ensuring the safety and conformity of goods and services, protecting the domestic market and expanding the country's foreign market, contributing to the development of new technologies and improving the competitiveness of the economy. By far, the most effective model is the European approach to technical regulation, which is based on the relevant harmonized legislation and promotes the free movement of goods, healthy competition, the introduction of innovation into production, but at the same time фensures the safety of products.
Keywords: презумпція відповідності; технічне регулювання